Impacts of climate change and afforestation on vegetation dynamic in the Mu Us Desert, China - Zenghui Sun (Elsevier, 2021)
As an important part of the terrestrial ecosystem, vegetation is commonly used as an indicator to evaluate climate change and ecological restoration efforts. In China’s farming-pastoral areas, the Mu Us Desert is a typical area utilizing desertification control methods where vegetation cover has significantly changed in recent years. It is important to assess how climate change and afforestation affect vegetation activity dynamic in this region. This study aims to investigate the relationship between vegetation and climate change by using the normalized difference vegetation index (NDVI), and to find the cause of vegetation change by performing multiple linear regression analysis in the Mu Us Desert (including 11 counties) during the period from 2000 to 2019. The results showed that NDVI of the growing season (May to October) across the whole region increased by 0.0058 per year during the 20-year study period. Correlation analysis between the NDVI and climatic factors indicated that precipitation, temperature and relative humidity had a significant positive correlation, and mean wind speed and sunshine hours had a significant negative correlation across the study area (except for mean wind speed in Shenmu and Yuyang). Stepwise multiple linear regression analysis indicated that the relative contribution by climatic factors and afforestation to NDVI change was 41.9% and 58.1% across the study area, respectively. Findings from our study may help to provide scientific support for decision making concerning ecological restoration management and policy efficiency estimation in other similar desert areas.